Hijacking the Mustard-Oil Bomb: How a Glucosinolate-Sequestering Flea Beetle Copes With Plant Myrosinases - Sporer, Theresa; Körnig, Johannes; Wielsch, Natalie; Gebauer-Jung, Steffi; Reichelt, Michael; Hupfer, Yvonne; Beran, Franziska (Frontiers in Plant Science, 2021)
Myrosinase enzymes play a key role in the chemical defense of plants of the order Brassicales. Upon herbivory, myrosinases hydrolyze the β-S-linked glucose moiety of glucosinolates, the characteristic secondary metabolites of brassicaceous plants, which leads to the formation of different toxic hydrolysis products. The specialist flea beetle, Phyllotreta armoraciae, is capable of accumulating high levels of glucosinolates in the body and can therefore at least partially avoid plant myrosinase activity. In feeding experiments with the myrosinase-deficient Arabidopsis thaliana tgg1×tgg2 (tgg) mutant and the corresponding Arabidopsis Col-0 wild type, we investigated the influence of plant myrosinase activity on the metabolic fate of ingested glucosinolates in adult P. armoraciae beetles. Arabidopsis myrosinases hydrolyzed a fraction of ingested glucosinolates and thereby reduced the glucosinolate sequestration rate by up to 50% in adult beetles. These results show that P. armoraciae cannot fully prevent glucosinolate hydrolysis; however, the exposure of adult beetles to glucosinolate hydrolysis products had no impact on the beetle’s energy budget under our experimental conditions. To understand how P. armoraciae can partially prevent glucosinolate hydrolysis, we analyzed the short-term fate of ingested glucosinolates and found them to be rapidly absorbed from the gut. In addition, we determined the fate of ingested Arabidopsis myrosinase enzymes in P. armoraciae. Although we detected Arabidopsis myrosinase protein in the feces, we found only traces of myrosinase activity, suggesting that P. armoraciae can inactivate plant myrosinases in the gut. Based on our findings we propose that the ability to tolerate plant myrosinase activity and a fast glucosinolate uptake mechanism represent key adaptations of P. armoraciae to their brassicaceous host plants.